Predicting academic success of engineering students in technical drawing from visualization test scores - Adanez, Gerardo Prieto; Velasco, Angela Dias [UNESP] (My University, 2002)
While observing the difficulties of first-year engineering students toward learning technical drawing, taking into account the progressively reduced work time with them, and recognizing the importance of spatial aptitude in the engineering profession, we feel the necessity to improve the teaching methodologies in this subject. In our opinion, in order to effectively plan the didactic process, it is necessary to detect as early as possible those students who require more attention and support. This study proposes an investigation of a visualization psychometric test that could facilitate an early diagnosis concerning the academic performance of technical drawing students. To this end, a computerized version of the Mental Cutting Test (MCT) was carried out on a sample of Brazilian engineering students from the Paulista State University at Guaratingueta Campus (UNESP) and from the Polytechnic School of Sao Paulo University (EPUSP). The test was analyzed by the Item Response Theory, with the Rasch model, a measurement model with optimal properties in order to estimate the level in spatial aptitude of the examinees. The results suggest that MCT can be useful in detecting those students with different performance levels in technical drawing.
Keywords: Rasch model; Spatial aptitude; Technical drawing